Design Adaptations in the Bathrooms for the Elderly Living in the Suburbs - Suastiwi Triatmodjo; Riza Septriani Dewi (Institut Seni Indonesia Denpasar, 2023)
The suitability of the bathroom design for the user, in this context, elderly people (elderly) is urgent. This urgency exists because a degenerative process has occurred, a decline in the quality of the elderly's body, and the elderly population continues to increase significantly. This study aims to find out the bathroom design approach model suitable for the elderly who live in the suburbs. By using practice-based research, this study has developed a conceptual bathroom design for the elderly who live in suburban areas and concludes that adaptive design is a suitable strategy to implement this design. In the future, this adaptive design strategy can also be applied to create various other spaces in homes for the elderly who live in the same or similar living environment.